Analyzing Barriers and Strategies to Improve Health Screening Implementation for Adults and Elderly - Pebriant Damayanti; Kodrat Pramudho; Ratih Purnamasari (Indonesian Journal of Global Health Research, 2026)
Non-communicable diseases (NCDs) such as hypertension, diabetes, and cardiovascular disease are major health problems in Indonesia, particularly among adults and the elderly. Health screening is essential for early detection, yet its implementation in primary health centers faces various challenges. This study aims to analyze barriers, supporting factors, and strategies to optimize health screening. This qualitative case study was conducted in five Puskesmas in Cilegon City, selected through purposive sampling. A total of 42 informants were involved, including Puskesmas heads, program managers, health workers, cadres, community members, and health office representatives. Data were collected using in-depth interviews, focus group discussions (FGDs), participatory observations, and document reviews. Data were analyzed thematically using Braun and Clarke’s framework, guided by the theories of Policy Implementation and the Theory of Planned Behavior (TPB). The main barriers included limited human resources, inadequate facilities, fragmented reporting systems, and low community awareness. Supporting factors were leadership commitment, active cadres, outreach innovations, integration with other services, and cross-sectoral collaboration. Optimizing health screening requires strengthening reporting systems, improving human resource capacity, cross-sectoral advocacy, and community-based approaches. Policy support, application integration, training, and local-level.